SIRТQI (MAXSUS SIRTQI) BO‘LIM TALABALARINING SESSIYA ORALIG‘I VAZIFALARI MAZMUNINI TAKOMILLASHTIRISH (chizma geometriya fani misolida) - Amirqulov, X.Q. (SCIENCE and SOCIETY, 2021)
This article is devoted to improving the content of the session tasks of the intermediate course on descriptive geometry for students of the correspondence course (special correspondence course) Department. As a result, the quality of control and consolidation of students ' knowledge is improved.
Keywords: extra mural students; term; tasks of continuous assessment complex; knowledge; assessment; graphic tasks; graphic literacy; graphic work; graphic task; consciousness; thinking; thought; special extra mural courses; imagination; test; exercise and task; surface; multilateral; independent work; creative work; electronic platform; descriptive geometry